2014
DOI: 10.1007/s10114-014-3590-9
|View full text |Cite
|
Sign up to set email alerts
|

Fixed points of multivalued quasi-nonexpansive mappings using a faster iterative process

Abstract: In this article, we prove some strong and weak convergence theorems for quasi-nonexpansive multivalued mappings in Banach spaces. The iterative process used is independent of Ishikawa iterative process and converges faster. Some examples are provided to validate our results. Our results extend and unify some results in the contemporary literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 14 publications
2
12
0
Order By: Relevance
“…With a series of numerical experiments and an analytical proof, it is established that the Picard-Ishikawa hybrid iterative process, recently introduced by Okeke [3], has the same rate of convergence as the CR iterative process, introduced by Chugh et al [8]. Our results improve, extend, and generalize several known results in the literature [18][19][20].…”
Section: Introductionsupporting
confidence: 77%
“…With a series of numerical experiments and an analytical proof, it is established that the Picard-Ishikawa hybrid iterative process, recently introduced by Okeke [3], has the same rate of convergence as the CR iterative process, introduced by Chugh et al [8]. Our results improve, extend, and generalize several known results in the literature [18][19][20].…”
Section: Introductionsupporting
confidence: 77%
“…They approximated fixed points by convergence of a Mann iterative process (a one-step process) applied on multivalued ρ-nonexpansive mappings in modular function spaces. Khan et al [7] constructed a three-step iterative process for multivalued mappings in Banach spaces. This process is independent of both Mann and Ishikawa iterative processes in the sense that neither reduce to the other.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the above lemma, Song and Wang [22] modified the iteration scheme used in [11] and improved the results presented therein. This scheme reads as follows:…”
Section: Introductionmentioning
confidence: 99%
“…al. [11] introduced new three iterative procedures and proved some strong and weak convergence theorems for quasi nonexpansive multivalued mappings in Banach spaces. They showed that the iterative process used is independent of Ishikawa iterative process and converges faster.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation